Dissatisfaction Desires and Deterioration Loneliness in Ernest Hemingway’s Cat in the Rain - Thulfiqar Abdulameer Sulaiman Alhmdni (Randwick International of Social Science Journal, 2024)
Like many great writers, Ernest Hemingway used short stories as a new genre of the 20th-century literature to comprehend human psychics in America after the first world war. Hemingway was worried about what could be called the effect of war on human desires. This research will study the dissatisfaction and isolation due to the consequences of war ghosts on Americans in a very short story, Cat in the Rain. The tactic could not be biographical but it depends on human dissatisfaction towards each other. This short story was written when the author was spending the holiday at a hotel in Italy with his lovely wife, gradually becoming alienated to Hadley (his wife). Oddly enough, the story displays a most insensitive spouse, on the other hand, the writer describes himself as extremely serious of masculine old-style satisfaction. The story can be understood as an essential notion in which a woman begins enquiring about her desires and wishes with no responses by the husband who prefers the material objects rather than spiritual ones. The dissatisfaction and alienation affected his lifestyle and way of living, through this story. The researcher is going to focus on the disharmony among spouses and the consequences of the deterioration of the war on Americans. This study reveals the crucial women’s needs while her husband spent most of his time away of the wife desires indifferent.